1991
DOI: 10.1007/bf00167379
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of muscarinic receptors mediating release of epithelial derived relaxant factor (EpDRF) in guinea-pig isolated trachea

Abstract: Muscarinic receptors mediating the release of epithelial derived relaxant factor (EpDRF) have been studied by using both contractions of the guinea-pig tracheal strip (with epithelium intact or denuded) or a coaxial bioassay assembly (rat anococcygeus-recipient; guinea-pig trachea-donor tissue). Indomethacin (1 microM/1) and physostigmine (0.1 microM/1) were both present throughout the study. In the tracheal strip studies, the potencies and maximal effects of all agonists studied (acetylcholine, arecoline, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It appears from these results, traction of guinea-pig trachea in the prese epithelium in response to acetic and car] esters and oxotremorine is mediated via m B values for tors. This is consistent with other findings (Eglen et al, 1991). pKB The augmentation of contraction of airway smooth muscle methoKtramine preparations to various agonists upon removal of the epi-30 mam thelium has suggested that it is stimulated release of a nonprostanoid EpDRF (s) that depresses muscle tone (Barnes et 5.7 ± 0.10 al., 1985; Flavahan et al, 1985).…”
Section: -4 -supporting
confidence: 90%
See 1 more Smart Citation
“…It appears from these results, traction of guinea-pig trachea in the prese epithelium in response to acetic and car] esters and oxotremorine is mediated via m B values for tors. This is consistent with other findings (Eglen et al, 1991). pKB The augmentation of contraction of airway smooth muscle methoKtramine preparations to various agonists upon removal of the epi-30 mam thelium has suggested that it is stimulated release of a nonprostanoid EpDRF (s) that depresses muscle tone (Barnes et 5.7 ± 0.10 al., 1985; Flavahan et al, 1985).…”
Section: -4 -supporting
confidence: 90%
“…The effect of remov-5.5 + 0.05 ing the epithelium on contraction to ACh may be mimicked , 1986). Also, indomethacin can impair the augmentation of contraction to acetic choline esters in this preparation 5.4± 0.06 (Eglen et al, 1991). In contrast, several studies have demonstrated that augmentation of contraction of guinea-pig tra-5.5 ± 0.06 chea to ACh and MCh upon removal of the epithelium is not 5+4 0.06 impaired by indomethacin (e.g.…”
Section: -4 -mentioning
confidence: 69%
“…Experiments were also carried out in a coaxial bioassay system with a slight modification of the methods described by Fernandes et al (10), Eglen et al (11), and Hay et al (12). This bioassay involved an epithelium-intact or denuded guinea-pig tracheal tube (donor tissue) and an epithelium-denuded tracheal strip (sensor strip).…”
Section: Tissue Preparationmentioning
confidence: 99%
“…As far as effects to exogenous cholinergic agents are concerned, the muscle responds to both muscarinic and nicotinic agonists. Muscarinic receptors located postjunctionally subserve contraction (Gillespie 1972;Oriowo 1983;Eglen et al 1991;Rand and Li 1993) and are also present on both noradrenergic and nitrergic nerve terminals where they subserve inhibition of transmission (Rajani and Gulati 1988;Li and Rand 1989). Activation of nicotinic receptors, which are present on noradrenergic and nitrergic nerve terminals, evokes release of the respective transmitters (Rand andLi 1992, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…; Li and Rand 1989) and the postjunctional receptors mediating contraction (M 2 , M 3 ? ; Li and Rand 1989;Oriowo 1983;Eglen et al 1991) in RAM may be of different subtypes. However, further work appeared to be required to clarify this issue unequivocally.…”
Section: Introductionmentioning
confidence: 99%